1983
DOI: 10.1037/h0080712
|View full text |Cite
|
Sign up to set email alerts
|

Effects of trainee expectancies and specific instructions on counselling skill acquisition.

Abstract: The present study entailed an examination of the acquisition of counselling skill by inexperienced, undergraduate counsellor trainees as a function of brief, specific instructions on how to counsel, and of the participants' prclraining expectancies pertaining to nondirectivc versus directive counselling style. The Reisman Direction-Unconscious motivation scale was used to identify high versus low directivencss expectancy participants, and the members of each of these iwo groups were randomly assigned to traini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1985
1985
2006
2006

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Some undergraduates in this study mentioned interviewing for information in their social psychology classes, whereas others expressed a familiarity with Rogerian humanistic psychology. Rappaport, Gross, and Lepper (1973) and Quartaro and Rennie (1983) have shown that specific instructions on interviewing enable college student volunteers to produce appropriate verbal interviewing behavior. It seems likely that some of the undergraduate counselors either directly or indirectly obtained information on prescribed counselor behavior and that this lead to some changes in postyear interview verbal responses.…”
Section: Discussionmentioning
confidence: 99%
“…Some undergraduates in this study mentioned interviewing for information in their social psychology classes, whereas others expressed a familiarity with Rogerian humanistic psychology. Rappaport, Gross, and Lepper (1973) and Quartaro and Rennie (1983) have shown that specific instructions on interviewing enable college student volunteers to produce appropriate verbal interviewing behavior. It seems likely that some of the undergraduate counselors either directly or indirectly obtained information on prescribed counselor behavior and that this lead to some changes in postyear interview verbal responses.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a few studies were found that investigated characteristics of trainees who profit most from training. These studies investigated dominance (Chasnoff, 1976), sex (Ronnestad, 1977), conceptual level (Berg & Stone, 1980), positive attitudes toward the target skill (Hirsch & Stone, 1982), and pretraining expectations for nondirective versus directive therapy style (Quartaro & Rennie, 1983). Unfortunately, no firm conclusions can be drawn about which trainee characteristics influence training outcome because these studies involved different trainee and target variables, and none of their findings have been replicated.…”
Section: Variables That Moderate the Effects Of Helping Skills Trainingmentioning
confidence: 99%
“…This "teaching to the test" may have artificially accentuated training effects when compared with no-training and may have confused training with the simple "cue-ing" of participants to produce predefined "correct" responses (cf. Quartaro & Rennie, 1983;Resnikoff, 1972).…”
Section: Overall Training Programsmentioning
confidence: 99%
“…Ivey (1971), on the other hand, proposed the teaching of counseling skills in a brief period (1–2 hr) and suggested that experiential learning is not necessary. Investigators evaluated these claims and compared the efficacy of the two training methods (Matarazzo, 1978; Perry, 1975; Toukmanian & Rennie, 1975; Toukmanian, Capelle, & Rennie, 1978; Quartaro & Rennie, 1983).…”
Section: Effective Modes Of Trainingmentioning
confidence: 99%